Evaluating Lower Limb Joint Flexion by Computerized Visual Tracking System and Compared with Electrogoniometer and Universal Goniometer - Chin Lim, Chee; Affandi, Marwan; Basah, Shafriza Nisha; Din, Mohamad Yazid (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
The lower limb joint’s range of motion (ROM) is an important clinical parameter used in diagnosing the severity level of lower limb joint injury. Along with the use of mechanical devices such as goniometer or electrogoniometer, motion capture and visual tracking has been increasingly deployed to aid the lower limb joint diagnosis. The universal goniometer can simply measure the joint angles. However, it has some limitations on allowing the clinician to analyze the ROM at the gate and track the lower limb joint. Motion capture devices are mainly used to analyze the patient’s joint flexion and assess the condition of the joints and bones. This study has used the visual tracking system (VTS), electrogoniometer (EGM) and universal goniometer (UGM) methods to examine the range of motion of 20 healthy subject volunteers. The results of three methods have been compared and discussed. The ROM result shows that VTS have the smallest SEM with averaged of 1.49 compared to EGM 3.41 and UGM 1.53. Thus, VTS give the high accurate in averaged lower limb flexion measurement. The result of joint flexion shows that left and right limb joint are similar for the healthy subject.